Pirfenidone exerts antifibrotic effects through inhibition of GLI transcription factors. Issue 5 (1st February 2017) - Didiasova, Miroslava; Singh, Rajeev; Wilhelm, Jochen; Kwapiszewska, Grazyna; Wujak, Lukasz; Zakrzewicz, Dariusz; Schaefer, Liliana; Markart, Philipp; Seeger, Werner; Lauth, Matthias; Wygrecka, Malgorzata
ABSTRACT: Pirfenidone is an antifibrotic drug, recently approved for the treatment of patients with idiopathic pulmonary fibrosis (IPF). Although pirfenidone exhibits anti‐inflammatory, antioxidant, and antifibrotic properties, the molecular mechanism underlying its protective effects remains unknown. Here, we link pirfenidone action with the regulation of the profibrotic hedgehog (Hh) signaling pathway. We demonstrate that pirfenidone selectively destabilizes the glioma‐associated oncogene homolog (GLI)2 protein, the primary activator of Hh‐mediated gene transcription. Consequently, pirfenidone decreases overall Hh pathway activity in patients with IPF and in patient‐derived primary lung fibroblasts and leads to diminished levels of Hh target genes, such as GLI1, Hh receptor Patched‐1, α‐smooth muscle actin, and fibronectin, and to reduced cell migration and proliferation. Interestingly, Hh‐triggered TGF‐β1 expression potentiated Hh responsiveness of primary lung fibroblasts by elevating the available pool of glioma‐associated oncogene homolog (GLI)1/GLI2, thus creating a vicious cycle of amplifying fibrotic processes. Because GLI transcription factors are not only crucial for Hh‐mediated changes but are also required as mediators of TGF‐β signaling, our findings suggest that pirfenidone exerts its clinically beneficial effects through dual Hh/TGF‐β inhibition by targeting the GLI2 protein.—Didiasova, M., Singh, R., Wilhelm, J., Kwapiszewska, G., Wujak, L., Zakrzewicz, D., Schaefer, L., Markart, P., Seeger, W., Lauth, M., Wygrecka, M. Pirfenidone exerts antifibrotic effects through inhibition of GLI transcription factors. FASEB J. 31, 1916–1928 (2017). www.fasebj.org